UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PENDIDIKAN AGAMA ISLAM - Anisatul Mutoharoh (CV. ADIBA AISHA AMIRA, 2024)
This study aims to describe the increase in student learning motivation in Islamic religious education subjects, this study uses qualitative research. Thus, the problem raised by the researcher is the effort to increase the learning motivation of fifth grade students of SDN Ketanggungan 07, Ketanggungan sub-district, Brebes Regency, totaling 26 people consisting of 12 boys and 14 girls. Islamic religious education has a very important role in understanding the noble character of students and also in improving the achievements of students because teachers have a responsibility in the teaching and learning process. One way to improve learning ability in Islamic religious education is to increase learning motivation. Because learning motivation plays a very important role in learning. Motivation encourages learning activities to achieve the expected goals. The author concludes that it is the duty of the teacher as a teacher to generate learning motivation in students, because motivation is one of the dynamic aspects that is very important. The existence of student learning motivation brings enthusiasm and learning becomes more fun and students are more focused on learning.